Learning about the teaching profession in the Early Childhood Education internship - Carvalho, Rodrigo Saballa de (2025)
Based on contributions from Studies on Teacher Education, the purpose of this dossier is to share contemporary discussions emerging from empirical and bibliographic research on the teaching-learning processes that occur during Early Childhood Education internships at Higher Education Institutions. The learnings of the teaching profession are understood as resulting from the personal and educational trajectories of the students, the knowledge acquired in the courses attended during the Pedagogy degree, experiences in non-curricular internships, as well as the actual teaching practice with children during the curricular internship.